Bowtie antenna for ground penetrating radar - Ong, Khye Liat (2006)
There are millions of abandoned landmines, useless and dangerous, still buried in many post-war areas. The conventional technique for landmines detection is the electromagnetic induction (EMI) sensors or metal detector. Ground Penetrating Radar (GPR) has to be used to detect these targets based on the change of dielectric permittivity rather than the metal content of the targets, thus is a viable technology for landmine detection. The antenna of a GPR plays a key role in radiating impulses into the ground with a minimal degree of distortion and loss. This thesis focuses on the design of such antenna based on bowtie configuration. The design starts with the conventional bowtie which was simulated using electromagnetic simulation software, SONNET. Investigations were carried out on the antenna with right offset feed locations, different ground plane sizes and different substrate layer thicknesses. The optimum feed location was found to be at 36 mm offset. The antenna exhibits dual resonances with narrow reflection bandwidth of 9 MHz or ~1.6 %. The 3 dB half-power beamwidth was broad, which is almost 90Â°. Larger ground plane improved the return loss of the antenna at the input, while broadening the reflection bandwidth. Similarly, increasing the thickness of the substrate layer was found to improve the reflection bandwidth, albeit worsened the return loss. However, the return losses were still good as the values were below the - 10 dB limit